Daddy's money : a memoir of farm and family - McDougall, Jo (University of Arkansas Press, 2011)
Jo McDougall lives in Leawood Kansas. She is the author of five books of poetry, including From Darkening Porches and Towns Facing Railroads (University of Arkansas Press).